Care Management Intervention to Address Determinants of Health for Individuals With Multiple Behavioral Health Readmission. Issue 2 (March 2022) - Hutchison, Shari L.; Herschell, Amy D.; Edwards, Jamie F.; Karpov, Irina; Wasilchak, Deborah S.; Hurford, Matthew O.
Abstract : Purpose of Study: To examine the effectiveness of a care management intervention to decrease readmissions and to better understand clinical and social determinants associated with readmission. Primary Practice Setting: Inpatient mental health (MH) and substance use disorder (SUD) facilities, nonhospital SUD withdrawal management and rehabilitation facilities. Methodology and Sample: The authors identified 3, 950 Medicaid-enrolled individuals who received the intervention from licensed clinical staff of a behavioral health managed care organization; 2, 182 individuals were eligible but did not receive the intervention, for treatment as usual (TAU). We used logistic regression to examine factors associated with readmission. Determinants of readmission were summarized through descriptive tests. Results: The intervention was associated with lower readmissions to SUD facilities compared with TAU (6.0% vs. 8.6%, p = .0002) and better follow-up to aftercare. Controlling for clinical differences between groups, regression results found increased odds of readmission for male gender (odds ratio [OR]: 1.33; 95% confidence interval [CI]: 1.16–1.52, p < .0001) and dual MH and SUD diagnoses (OR: 1.52; CI: 1.29–1.79, p < .0001). Prior inpatient and case management services were also associated with increased odds for readmission. In the regression model, the intervention was not associated with decreased odds for readmission. Individuals with readmission ( n = 796) were more likely to report being prescribed psychotropic medication and having housing difficulties and less likely to report having a recovery plan than those without readmission. Implications for Case Management Practice: Characteristics of Medicaid populations with hospitalization may contribute to readmission, which may be mitigated through care management intervention.